ANALISIS PENGETAHUAN GURU PAUD/TK TENTANG SDIDTK DENGAN PELAKSANAAN DETEKSI PENYIMPANGAN PERKEMBANGAN BALITA - Suryandari, Artathi Eka; Purwanti, Sugi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
The first years of life up to the age of two years are the golden period. Optimal development can be achieved by providing adequate nutrition, proper parenting, socialization and stimulation, so it should be anticipated by monitoring developments to find early deviations. Early detection of developmental deviations using SDIDTK can be performed by health personnel, teachers of kindergarten, and health cadres who have received training. Based on interviews that researchers do to 10 teachers of kindergarten 7 people have never heard of SDIDTK and have never done early detection of developmental deviations in their students. Objective: To analyze the knowledge of teachers of kindergarten on SDIDTK with the implementation of early detection of developmental deviations. This research used observational method with cross sectional approach. The population in this study is teachers of kindergartens in South of Purwokerto sub district is 90 people. The sample of research is 47 people, research instrument in the form of questionnaire contains 20 questions and chi square data analysis techniques. Result of research most of knowledge of respondent in good category that is equal to 70, 21%. Most respondents did not do early detection of developmental deviation (61.70%). The result of the analysis is the relationship between the knowledge ofÂ  teachers of kindergarten on SDIDTK with the implementation of detection of development deviation with Ï value 0.05. Key Words: SDIDTK, knowledge, teacher of Kindergarten